2020
DOI: 10.29309/tpmj/2020.27.10.4397
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of adverse perinatal outcome in patients with poor biophysical profile.

Abstract: Objectives: To find out the frequency of adverse perinatal outcome among patients having poor BPP. Study Design: Descriptive study. Setting: Nishtar Hospital Multan. Period: From August 2018 to November 2019. Material & Method: In this study, 273 cases fulfilling the inclusion criteria were enrolled. They were screened on the basis of biophysical profile on ultrasonography to confirm the poor biophysical profile. Patients were followed till delivery. Adverse perinatal outcome i.e. cesarean section and poor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
0
1
Order By: Relevance
“…In this study, 88 out of 133 (66.2%) of the participants enrolled had a reactive NST finding, compared to 45 out of 133 (33.8%) participants who had a non-reactive NST finding. This compares to findings from Saudi Arabia, 6 which reported that 32.9% of the participants had a non-reactive NST finding. Contrasting findings were observed in studies reviewed from Ireland 7 and Kolkata, India, 8 which reported a nearly uniform finding of reactive NST among the females enrolled.…”
Section: Discussioncontrasting
confidence: 82%
“…In this study, 88 out of 133 (66.2%) of the participants enrolled had a reactive NST finding, compared to 45 out of 133 (33.8%) participants who had a non-reactive NST finding. This compares to findings from Saudi Arabia, 6 which reported that 32.9% of the participants had a non-reactive NST finding. Contrasting findings were observed in studies reviewed from Ireland 7 and Kolkata, India, 8 which reported a nearly uniform finding of reactive NST among the females enrolled.…”
Section: Discussioncontrasting
confidence: 82%